123I-FP-CIT SPECT Accurately Distinguishes Parkinsonian From Cerebellar Variant of Multiple System Atrophy. (February 2018) - Nicastro, Nicolas; Garibotto, Valentina; Burkhard, Pierre R.
Abstract : Purpose: Dopamine transporter SPECT imaging is a valuable tool to estimate the integrity of presynaptic dopaminergic pathways in degenerative parkinsonisms. Evidence about SPECT differential pattern between parkinsonian and cerebellar forms of multiple system atrophy (MSA-P and MSA-C) is lacking. We aimed at assessing whether MSA-P and MSA-C variants have a distinct semiquantitative 123 I-FP-CIT SPECT pattern. Methods: We studied a unicentric 13-year (2003–2016) retrospective cohort of subjects with possible or probable MSA and scanned with the same acquisition and reconstruction SPECT protocol. Age-dependent semiquantitative reference limits for striatal volumes of interest, asymmetry indices, and caudate/putamen ratio were previously established with a percentile approach on a cohort of subjects with nondegenerative conditions and normal visual scan. Results: Thirty-four subjects with clinical MSA (28 MSA-P and 6 MSA-C) were identified (mean age, 68.2 ± 10.1 years; male/female ratio 1.00; disease duration, 2.5 ± 2.2 years; Movement Disorders Society Unified Parkinson's Disease Rating Scale III score, 33.8 ± 12.4). The MSA-P subjects exhibited lower uptake values for all volumes of interest, for example, striatal uptake on the more affected side (1.10 ± 0.51) compared with MSA-C (2.30 ± 0.41, P = 0.0005), as well as significantly higher asymmetry indices % (24.7 ± 24.8 vs 6.3 ± 4.5, P = 0.028) and caudate/putamen ratio (2.26 ± 1.23 vs 1.13 ± 0.17, P = 0.00148). Conclusions: The MSA-P and MSA-C subjects exhibited significantly distinct semiquantitative SPECT pattern with severe uptake impairment and high asymmetry for MSA-P and borderline uptake values for MSA-C. Clinical distinction of these 2 phenotypical entities is necessary in order to evaluate SPECT potential to discriminate between degenerative parkinsonisms.